1956
DOI: 10.6028/jres.057.027
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrum of sulfur vapor

Abstract: The mass spect rum of sulfur vapor has been measu red by evapo ra t in g sulfur from a heated t ube directly in to t he ionization chambe r of a mass sp ectrometer. I ons S;; w it h x ra nging fro m 1 to 8 are obse rved with St most ab unda n t. I sotopc ab undances we re comp uted f rom t he S;-ions. The appearance p otentials of S: and St are respectIvcl.v 8.9 ± 0.2 a nd 8.3 ± 0.2 electron volts. This suggests t hat t he vapor in t he ioni zation chamber is a mixture of molec ules co ntaining S2 a nd S8 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1958
1958
2003
2003

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…In 1809, the French chemists Louis-Joseph Gay-Lussac and Louis-Jacques Thenard proved the elemental nature of sulfur. In its 1961 report [22], CAWIA recommended A r (S) = 32.064(3) based on the abundances of S isotopes in virgin Texas sulfur reported by Bradt et al [253] and in meteoritic S reported by MacNamara and Thode [254], with atomic masses from Everling et al [23]. CAWIA observed that this value was in good agreement with the results of chemical determinations and that the uncertainty was assigned largely on the basis of natural variability, as documented by Rankama [255] and Duckworth [256].…”
Section: S Sulfurmentioning
confidence: 99%
“…In 1809, the French chemists Louis-Joseph Gay-Lussac and Louis-Jacques Thenard proved the elemental nature of sulfur. In its 1961 report [22], CAWIA recommended A r (S) = 32.064(3) based on the abundances of S isotopes in virgin Texas sulfur reported by Bradt et al [253] and in meteoritic S reported by MacNamara and Thode [254], with atomic masses from Everling et al [23]. CAWIA observed that this value was in good agreement with the results of chemical determinations and that the uncertainty was assigned largely on the basis of natural variability, as documented by Rankama [255] and Duckworth [256].…”
Section: S Sulfurmentioning
confidence: 99%
“…S, Sz, H2S, HzSz falls into line with the series I.P. 0 , 02, HzO, HzOz, though such comparisons have been used t o justify the correctness of values obtained (27,30).…”
Section: Experiments On S2omentioning
confidence: 95%
“…Sz exist between 8.3 v and 11.0 v (27)(28)(29)(30)(31), while the only published value of I.P. H2S2 (10.2 v) has been obtained indirectly (30).…”
Section: Experiments On S2omentioning
confidence: 99%
See 1 more Smart Citation
“…The ~I a s S pe ctrometr.\-Section has published several papers on detection and analy is of heavy mole cules evaporated from a vacuum-tub e furnac e dire ctly into the ionization chamber of a ma s spectrom eter [1, 2,3,4).1 l\lixture of heavy molecules have b een st udied by r eco rding t he spectra as t he temperature is increa ed step b~-step. This afford th e advantage t hat the mixture i fractionated in the proce s of evaporation and t he complexity of the mass pectra is redu ced .…”
Section: Introductionmentioning
confidence: 99%